Control of voluntary and reflexive saccades. - Walker, R; Walker, D; Husain, M; Kennard, C (2000)
The latency of 'reflexive' saccades (made in response to peripheral visual stimuli) was compared to that of 'voluntary' saccades performed in anti-saccade and symbolically cued paradigms. Manipulation of visual events at fixation was carefully controlled across all conditions. Reflexive saccade latency was significantly faster than the latency of all forms of voluntary saccades. Importantly, the latency of saccades made after presentation of a symbolic cue at central fixation (voluntary arrow-cue condition) was greater than that made in the anti-saccade paradigm that requires suppression of a reflexive response. It is suggested that the increase in latency of saccades made in the voluntary arrow-cue condition may reflect differences in programming a 'When' trigger signal for saccades made in the absence of a peripheral stimulus.